Estimation of glucosamine in biomass of Trichoderma reesei cultivated on lignocellulosic substrates - Teerin Chysirichote; Waraporn Mapisansup; Soysrung Aroonsong (Journal of Basic Microbiology, 2021)
Effects of the compositions of lignocellulosic substrate including hemicellulose, cellulose, lignin, and protein on the glucosamine content in biomass of Trichoderma reesei TISTR3080 were studied. A synthetic solid surface media containing different ratios of xylan (hemicellulose), carboxymethyl cellulose (cellulose), lignin, and various concentrations of yeast extract (source of protein) were used to cultivated T. reesei. Regression analysis identified significant individual and interaction factors that affected glucosamine quantity in T. reesei biomass. A regression model was developed to estimate the glucosamine content in biomass of T. reesei from the compositions of the lignocellulosic substrate. An acceptable error (not more than 10%) of the regression model was obtained from validation with the experimental results of glucosamine content in biomass of T. reesei cultivated on lignocellulosic solid surface media made from copra waste and banana peel.
Keywords: Biofuel production and bioconversion; Microbial Metabolic Engineering and Bioproduction; Enzyme Production and Characterization